连接至通信网络和切换网络连接性的方法 (2024)
本申请涉及连接至通信网络和切换网络连接性的方法。所公开的主题的实现提供了经由自主移动装置的通信接口而连接至第一通信网络和第二通信网络这两者的方法。在通信接口断开的情况下，可以连接至第三通信网络。可以存储地图，该地图包括自主移动装置所位于的能够接入多个通信网络的一个或多个第一位置，以及包括自主移动装置所位于的多个通信网络中的一个以上通信网络已被断开的一个或多个第二位置。在自主移动装置位于通信网络已断开的位置其中之一的预定距离内的不同时间，可以基于地图而切换至第三通信网络或多个通信网络中的另一通信网络。 Implementations of the disclosed subject matter provide a method of connecting, via a communications interface of an autonomous mobile device, to both a first communication network and a second communication network. A third communication network may be connected to when the communications interface is disconnected. A map may be stored that includes a first one or more locations of the autonomous mobile device where the plurality of communications networks are accessible, and includes a second one or more locations of the autonomous mobile device where one or more of the plurality of communications networks have been disconnected. At a different time, when the autonomous mobile device is within a predetermined distance of one of the locations that the communica